Social death of older adults residing in nursing homes in Finland - Paananen, Jenny; Kulmala, Jenni; Pirhonen, Jari (Elsevier, 2025)
Social death refers to situations in which individuals become socially excluded from social interaction or are considered socially insignificant. Social death is about losing roles, relationships, and eventually identity in the eyes of others. When becoming a permanent resident in a nursing home, older adults face an increased risk of social death. However, empirical research on social death and its manifestations in nursing homes is still scarce. The aim of this study was to investigate the phenomenon of social death by interviewing family members (N = 19) of older people living in nursing homes in Finland. A theory-driven thematic analysis of family members' interviews revealed two cross-cutting themes that were linked to social death in nursing homes. We discovered that 1) the transition to a nursing home significantly narrowed the older adults' social environment and 2) dementia seemed to affect all aspects of older adults' social life and social agency negatively. Furthermore, four main mechanisms of social death in nursing homes were 1) losses associated with decline of physical and mental health, 2) loss of social identity, 3) isolation and lack of social connectedness, and 4) lack of quality of care. It seems that nursing home residents, especially those with advanced dementia, face social death because they are not seen as persons who are entitled to social roles and meaningful activities. Thus, there is an urgent need to improve the social connectedness of all older adults living in care facilities, with particular attention to those with memory loss. Based on these results, we provide checklists for nursing professionals and all citizens to restore the social value of older persons.